A New Useful Exponential Model with Applications to Quality Control and Actuarial Data. (9th June 2022) - Fayomi, Aisha; Tahir, M. H.; Algarni, Ali; Imran, M.; Jamal, Farrukh
Abstract : The compounding approach is used to introduce a new family of distributions called exponentiated Bell G, analogy to exponentiated G Poisson . Several essential properties of the proposed family are obtained. The special model called exponentiated Bell exponential (EBellE) is presented along with properties. Furthermore, the risk theory related measures including value-at-risk and expected-shortfall are also computed for the special model. Group acceptance sampling plan is designed when a lifetime of a product or item follows an EBellE model taking median as a quality parameter. The parameters of the proposed model are estimated by considering maximum likelihood approach along with simulation analysis. The usefulness of the proposed model is illustrated by practical means which yield better fits as compared to several exponential related extended models.